A National Survey of U.S. Adolescent Sleep Duration, Timing, and Social Jetlag During the COVID-19 Pandemic. Issue 3 (4th May 2023) - L. Wesley, Katherine; Cooper, Emily H.; Brinton, John T.; Meier, Maxene; Honaker, Sarah; Simon, Stacey L.
ABSTRACT: Objectives: To assess changes in duration, timing, and social jetlag in adolescent sleep during the COVID-19 pandemic and evaluate the impact of mood, physical activity, and social interactions on sleep. Study Design: An online survey queried adolescents' sleep before (through retrospective report) and during the initial phase of COVID-19 in May 2020. Adolescents (N = 3, 494), 13–19 years old, in the United States (U.S.) answered questions about their current and retrospective (prior to COVID-19) sleep, chronotype, mood, and physical and social activities. Linear regression models were fit for time in bed, reported bed and wake times, and social jetlag during COVID-19, accounting for pre-COVID-19 values. Results: Total reported time in bed (a proxy for sleep duration) increased on weekdays by an average of 1.3 ± 1.8 hours (p < .001) during COVID-19, compared to retrospective report of time in bed prior to COVID-19. During COVID-19, 81.3% of adolescents reported spending 8 hours or more in bed on weekdays compared to only 53.5% prior to COVID-19. On weekdays, bedtimes were delayed on average by 2.5 hours and wake times by 3.8 hours during COVID-19 compared to prior to COVID-19. On weekends, bedtimes were delayed on average by 1.6 hours and waketimes by 1.5 hours (all p's < 0.001). Social jetlag of >2 hours decreased to 6.3% during COVID-19 compared to 52.1% prior to COVID-19. Anxiety and depression symptoms and a decline in physical activity during COVID-19 were associated with delayed bed and wake times during COVID-19. Conclusions: During COVID-19, adolescents reported spending more time in bed, with most adolescents reporting 8 hours of sleep opportunity and more consistent sleep schedules. As schools return to in-person learning, additional research should examine how sleep schedules may change due to school start times and what lessons can be learned from changes that occurred during COVID-19 that promote favorable adolescent sleep.